BELAJAR JADI GURU, BELAJAR JADI TELADAN: CERITA PPL DI SMA NEGERI 2 MERANGIN - Ade Taufan; Ade Susanti; Hardianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Teaching Practice Program (PPL) is an essential component of teacher education designed to provide pre-service teachers with real teaching experiences in schools. This program was carried out at SMA Negeri 2 Merangin from September 22 to November 11, 2025, focusing on the implementation of a student discipline and character-building program. During the program, students from the Faculty of Teacher Training and Education, University of Merangin, actively participated in classroom instruction, character development activities, and various school programs such as morning assemblies, physical exercises, and the “Clean and Orderly Friday” initiative. The results showed a noticeable improvement in students’ discipline, including punctuality, neatness, and adherence to school regulations. The PPL participants also served as role models and mentors, positively influencing students’ attitudes and behavior. Furthermore, this program provided valuable learning experiences for the pre-service teachers in understanding the teacher’s role not only as an instructor but also as a moral guide who fosters responsibility, order, and ethics. Overall, the PPL implementation at SMA Negeri 2 Merangin offered meaningful professional experiences for the pre-service teachers while strengthening collaboration between the school and the university in developing future educators who are disciplined, ethical, and committed to excellence.